2005
DOI: 10.1007/s10498-004-4765-2
|View full text |Cite
|
Sign up to set email alerts
|

Fe–Al–organic Colloids Control of Trace Elements in Peat Soil Solutions: Results of Ultrafiltration and Dialysis

Abstract: Size fractionation of $40 major and trace elements (TE) in peat soil solutions from the Tverskaya region (Russia) has been studied using frontal filtration and ultrafiltration through a progressively decreasing pore size (5, 2.5, 0.22 lm, 100, 10, 5, and 1 kD) and in situ dialysis through 6-8 and 1 kD membranes with subsequent analysis by ICP-MS. In (ultra) filter-passed permeates and dialysates of soil solutions, Fe, Al, and organic carbon (OC) are well correlated, indicating the presence of mixed organo-mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
86
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(112 citation statements)
references
References 103 publications
(101 reference statements)
23
86
1
2
Order By: Relevance
“…Similar technique has been used to account for metal speciation both in the water column and in the pore waters (Carignan et al, 1985;Alfaro-De la Torre et al, 2000;Gimpel et al, 2003). The duration of this dialysis procedure was between 24 and 48 h. Pokrovsky et al (2005) showed in laboratory experiments that, for both 1 and 6-8 kDa membranes, an equilibrium distribution is attained within 6-12 h, in agreement with the manufacturer's specifications. At the same time, Carignan et al (1985) argued that much longer equilibration time is necessary to achieve equilibrium dialysis distribution in porewaters.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…Similar technique has been used to account for metal speciation both in the water column and in the pore waters (Carignan et al, 1985;Alfaro-De la Torre et al, 2000;Gimpel et al, 2003). The duration of this dialysis procedure was between 24 and 48 h. Pokrovsky et al (2005) showed in laboratory experiments that, for both 1 and 6-8 kDa membranes, an equilibrium distribution is attained within 6-12 h, in agreement with the manufacturer's specifications. At the same time, Carignan et al (1985) argued that much longer equilibration time is necessary to achieve equilibrium dialysis distribution in porewaters.…”
Section: Methodsmentioning
confidence: 77%
“…Another important environmental issue is the fate of organic carbon in lakes that is likely to significantly control the CO 2 balance in high latitudes (Smith et al, 2004;Shirokova et al, 2009). High concentrations of dissolved organic matter (DOM) and thus, the colloidal status of most trace elements (TE) is the most important characteristic feature of TE geochemistry in European Russian Arctic zone (Pokrovsky and Schott, 2002;Pokrovsky et al, 2005). This change in metal speciation (i.e., the proportion of organo-mineral colloids and humic/fulvic complexes of trace metals, size distribution in colloidal fraction) between different water reservoirs or in the water column is expected to be controlled by: (1) biological processes of primary production/mineralisation and the release of organic exudates, both on diurnal (photosynthesis) and monthly (summer bloom, spring and autumn overturn) scales occurring in the water column; and (2) hydrological conditions of the watershed that controls the delivery of allochtonous organic matter from the soil reservoirs via riverine inflow, which in turn, depends on intra-soil processes, watershed lithology, and, if present, anthropogenic and atmospheric input.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, the Fe colloids appear to be missing in the riparian zone, leaving only the organic colloids as possible carriers (Neubauer et al, 2013). There is also strong evidence that organic matter is responsible for carrying a wide range of elements in boreal waters (e.g Gustafsson et al, 2000;Pokrovsky et al, 2005;Andersson et al, 2006;Dahlqvist et al, 2007;Pokrovsky et al, 2010;Vasyukova et al, 2010;Aiken et al, 2011). Furthermore, it has been demonstrated that the affinity for organic matter of various metals is essential for understanding their transport and spatial variability in the boreal landscape .…”
Section: Enrichment In the Riparian Zonementioning
confidence: 97%
“…5), enhanced mobilisation of soil organic matter and transport of terrestrial DOC to the limnic ecosystems and the North Sea are likely. Dissolved organic matter affects ecosystem nutrient availability (Carpenter et al 2005), acidification of limnic systems (Oliver et al 1983) and solubility, transport and toxicity of heavy metals and organic pollutants (Carter and Suffet 1982;Pokrovsky et al 2005). It also regulates the photochemistry of natural waters (Zafiriou et al 1984) and influences aquatic production of algae and bacteria (Wetzel 1992;Carpenter and Pace 1997).…”
Section: Inland Ecosystems and The Wider North Sea Systemmentioning
confidence: 99%